BOD5 and TOC at river crossings, East Coast Highway, Peninsular Malaysia. - Yusoff, Mohd Kamil; Ramli, Mohammad Firuz; Juahir, Hafizan; Kwong, Siew San; Abd Manaf, Latifah; Tengku Ismail, Tengku Hanidza; Harun, Rostam (International Association for Environmental Hydrology, 2008)
This paper evaluates the Biochemical Oxygen Demand (BOD5) and Total Organic Carbon (TOC) levels at river crossings due to East-Coast highway development. High concentrations of organic contents in the aquatic environment contribute to river water pollution. Thirty three samples were collected at the selected river crossings along the East-Coast Highway. Results showed that there was no significant linear relationship between BOD5 and TOC. Results from the t-test indicated that the construction of the East-Coast Highway has a negative impact as shown by BOD5. The results suggested that more samples should be collected over a longer duration to establish a more reliable relationship between the two parameters.